Prevalence and temporal trends of presarcopenia metrics and related body composition measurements from the 1999 to 2006 NHANES - Li, Ji-Bin (BMJ Open, 2020)
OBJECTIVE: To evaluate the prevalence and temporal trends of presarcopenia and related body composition measurements. DESIGN: Cross-sectional study. SETTING: National Health and Nutrition Examination Survey (NHANES) 1999–2006. METHODS: Presarcopenia was defined according to the guidelines from the European Working Group on Sarcopenia. Logistic or linear regression models were used to evaluate the linear trend of the prevalence of presarcopenia, obesity and related body composition measurements. PARTICIPANTS: A total of 29 947 participants aged 18–90 years from five waves of the NHANES were included in the analysis. OUTCOME MEASURES: Presarcopenia was sex-specifically defined as having a skeletal mass index ≤7.26 kg/m(2) in men and ≤5.5 kg/m(2) in women. Body composition measurements, including total body fat percentage, total body fat mass, total lean body mass, appendicular skeletal muscle mass and bone mineral density, were obtained by dual-energy X-ray absorptiometry. RESULTS: The overall prevalence of presarcopenia ranged from 16.4% in 1999–2000 to 14.8% in 2005–2006 (p for trend=0.78). Presarcopenia was stable in both males (p for trend=0.36) and females (p for trend=0.20). The presarcopenia prevalence was significantly elevated among the age group of 18–39 years old (from 11.3% to 14.1%, p for trend=0.04) and among non-Hispanic blacks (p for trend <0.001). Adults aged ≥80 years old had the highest prevalence. CONCLUSIONS: The prevalence of presarcopenia increased among young individuals over time. Non-Hispanic blacks also demonstrated an increasing trend in the prevalence over time.